Analisis Kinerja Karyawan terhadap Kepuasan dan Kepercayaan Pelanggan dalam Penjualan Motor Bekas di Nico Garage 88 - Ni Ketut Arniti; Komang Dio Surya Kusuma (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines how employee performance influences customer satisfaction and trust in the used motorcycle sales process at Nico Garage 88, Denpasar. The research applies a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with the owner, employees, and customers, as well as direct observation at the showroom during January to March 2025. The findings reveal that employee performance plays a significant role in shaping customer experiences. Although some employees deliver good service, inconsistencies remain in responsiveness, communication, and professionalism. Customers are generally satisfied with the motorcycle quality and pricing, yet inconsistent service reduces their overall satisfaction. Furthermore, customer trust grows when employees provide transparent, honest, and detailed information about the motorcycles. Conversely, unclear explanations and inattentive attitudes can create doubt. This research emphasizes the need for continuous improvement in employee performance through communication training, professional conduct, and consistent service delivery to strengthen customer satisfaction and trust.